Avoidance the Norms of Legislation as Manifestation of the Deviant Behavior of Participants of Civil Relations - YURKEVYCH, Yurii M.; KRASNYTSKYI, Ivan V.; MAIKUT, Khrystyna V. (Journal of Advanced Research in Law and Economics, 2019)
Under conditions of the market relations’ development, the growth of social standards, the legislature’s active work, the level of regulation of social relations has increased. In spite of the high level of regulation of the outlined aspects, the participants of civil relations do not always follow the normative rules. Such deviant behavior is caused by various factors. The purpose of this scholarly article is to study the issues of avoidance the norms of law as a manifestation of deviant behavior of participants in civil relations, as well as to develop proposals to prevent its further manifestation. This study has focused on the delinquent type of deviant behavior in social relations. It has been concluded that the deviant behavior of civil relations participants, which is aimed at avoidance the legislative regulation, can be divided into two types: behavior that contains indirect violations of regulations and behavior that does not contain formal violations of regulations. For a better understanding of the causes and factors that cause the phenomena under study, such concepts as ‘legal conscience’ and ‘legal culture’ have been analyzed.